Sustainable Consumption Design, Innovation and Practice - Genus, Audley; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book originates from the work of contributors to initiatives and global networks promoting and pursuing lines of enquiry that recognise and probe relationships between sustainable consumption, design and production, and the implications of those relationships for new economic activity and the way we live and govern ourselves. It features contributions from social scientists (e.g. from the fields of innovation studies, geography, environmental policy and sociology) and practitioners, serving to generate a short-list of research perspectives and topics around which future research and actions in practice will be orientated. The book consists of ten chapters divided into three parts, focusing on: perspectives/methodological insights; empirical work integrating consumption and production; and site-specific practitioner-oriented case studies. The conclusion examines the key aspects of policy, research and practical implications.
Keywords: Environment; Environmental law; Environmental policy; Social sciences; Human geography; Environment; Environmental Law/Policy/Ecojustice.; Human Geography; Methodology of the Social Sciences; Electronic books